Maisy goes to the museum - Cousins, Lucy. (Somerville, Mass. : Candlewick Press, 2009)
Maisy and her friends spend a rainy day exploring the museum.
"A Maisy first experiences book"--Cover.
First published: London : Walker Books Ltd.
Booklist
Horn Book
School Library Journal
Booklist, October 2008
Keywords: Animals -- Juvenile fiction; Maisy (Fictitious character : Cousins) -- Juvenile fiction; Museums -- Juvenile fiction; Animals -- Fiction; Maisy (Fictitious character : Cousins) -- Fiction; Museums -- Fiction; Animals -- Fiction; Maisy (Fictional character : Cousins) -- Fiction; Museums -- Fiction